2016
DOI: 10.1097/md.0000000000005506
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of the Birmingham Vasculitis Activity Score (BVAS) with systemic vasculitis patients transferred to the intensive care unit (ICU)

Abstract: Systemic vasculitides represent a heterogeneous group of diseases that share clinical features including respiratory distress, renal dysfunction, and neurologic disorders. These diseases may often cause life-threatening complications requiring admission to an intensive care unit (ICU). The aim of the study was to evaluate the validity and responsiveness of Birmingham Vasculitis Activity Score (BVAS) score to predict survival in patients with systemic vasculitides admitted to ICU.A retrospective study was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 33 publications
1
20
1
Order By: Relevance
“…Burkhardt et al reported similar results in patients with Wegener's granulomatosis [19]. Some studies have shown a relationship between vasculitic activity and long-term and short-term (such as in ICU mortality) prognosis [20,21]. BVAS score has been used most frequently in these studies.…”
Section: Discussionmentioning
confidence: 91%
“…Burkhardt et al reported similar results in patients with Wegener's granulomatosis [19]. Some studies have shown a relationship between vasculitic activity and long-term and short-term (such as in ICU mortality) prognosis [20,21]. BVAS score has been used most frequently in these studies.…”
Section: Discussionmentioning
confidence: 91%
“…24 Patients with anti-peroxidasin antibodies had significantly worse vasculitis activity ( Figure 4B; median 12 versus 2; P=0.02), and had a median score above values associated with substantially increased intensive care unit mortality. 25…”
Section: Resultsmentioning
confidence: 99%
“…28 A literature search on mortality of vasculitis patients under intensive care only brought up studies on ICU treatment in general. [4][5][6][7][8]10,[21][22][23][24] Investigations on ICU treatment for sepsis in particular are missing. We have found differing results while comparing our mortality to that in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Contrary to patients with Rheumatoid Arthritis, 20 investigations on vasculitis and intensive care treatment for sepsis are scarce or address ICU treatment in general without focusing on sepsis in particular. [4][5][6][7][8]10,[21][22][23][24] We therefore planned to investigate retrospectively the outcome of sepsis in necrotizing vasculitis patients requiring intensive care treatment in a university hospital in Germany.…”
Section: Introductionmentioning
confidence: 99%